Exploring New Horizons and Challenges for Social Studies in a New Normal Proceedings of the International Conference on Social Studies and Educational Issues, (ICOSSEI 2021), Malang City, Indonesia, 7 July 2021 - Purnomo, Agus; Sismat, Muhamad Alif Haji; Isma'il, Zawawi; Sringernyuang, Luechai (Taylor & Francis, 2022)
The new standards and changes exist in social science studies. Covid 19, especially in Indonesia, at the end of 2019, has an impact on changes in every sector of life. This change is a form of community adaptation. Therefore, this conference aims to explore theoretical and practical developments of the social sciences, to build academic networks while gathering academics from various research institutes and universities. This book provides the new standard and encourages many thoughts in theoretical and empirical studies in the social field. The scope that can be generated in this standard includes patterns, opportunities, and challenges in social science, learning to new standards, learning innovation, and implementing new learning standards in Indonesia, which was adopted in the form of the Merdeka Belajar program. The study results will fill the gaps in knowledge in the new social life and social science. Therefore, this book aims to mediate the researchers in the same field to discuss and find solutions to current issues in the social field and build cooperation and synergy in creative ideas to work together to create joint research. This book will be interesting to students, scholars, and practitioners who have a deep concern in social science. It is futuristic with a lot of practical insights for the students, faculty, and practitioners. Since the contributors are from across the globe, it is fascinating to see the global benchmarks.